Perancangan dan Pembuatan Aplikasi Peta Interaktif Universitas Kristen Petra Berbasis Android - Halim, Christopher Imantaka; Intan, Rolly; -, Liliana (Jurnal Infra, 2014)
Along with the growth of Petra Christian University, more college students and guests will come to visit this university. Petra Christian University has more than few buildings and it does not rule out the possibility that new buildings will be build later. Then, Petra Christian University will need location maps and directions to help visitors of the university find specific locations inside campus area. There are physical and digital maps of Petra Christian University, and a Final Project which displays few floor maps of Petra Christian University. But an application which especially provides an interactive map and virtual tour of Petra Christian University hasnât been made.Thus, a system is being developed, which has two separate applications. The first application is an Android-based apllication called Petra PanoraMap, its goal is to provide interactive maps for Petra Christian University. This application provides a virtual tour for users which displays panoramic views of several locations inside Petra Christian University. The second application is a web-based application called PanoraMap Editor, its goal is to provide all data and pictures needed by Petra PanoraMap. Thus, it is needed to create a data structure that can represent Petra Christian University as a whole entity based on object-oriented approach.Tests have been performed to both Petra PanoraMap and PanoraMap Editor. Petra PanoraMap application can display panoramic views so that users can feel that they are inside Petra Christian University. It is proved that PanoraMap Editor application can produce a type of data that can readily deployed into and read by Petra PanoraMap, so that contents and panoramic photos inside Petra PanoraMap is a dynamic data.